Asymptomatic cerebral infarction in a surviving twin - Lai, Chi-Chieh; Huang, Wen-Chin; Kao, Hung-Wen; Lee, Chuen-Ming (Journal of Pediatric Neurology, 2007)
Single fetal death for a twin pregnancy is often associated with multiple organ damage for the surviving twin, especially involving the central nervous system. The surviving twin may reveal normal neural function incipiently and its condition can easily remain undiagnosed. Herein, we present the case of a surviving twin complicated with asymptomatic unilateral cerebral infarction, and featuring the concomitant intrauterine demise of the other fetus, magnetic resonance angiography for the survivor revealing no evidence of narrowing of cerebral vessels.
Keywords: Cerebral infarction; intrauterine death of twin fetus; twin pregnancy